Training on using electricity monitoring instruments for MSMEs in achieving sustainable energy efficiency in Legok Village - Saputri, Fahmy Rinanda; Fianty, Melissa Indah; Tampubolon, Marojahan (Community Empowerment, 2025)
Culinary MSMEs (Micro, Small, and Medium Enterprises) in Legok Village face challenges in managing energy consumption efficiently, resulting in higher operational costs. These challenges are due to a lack of tools to monitor energy use and limited knowledge of advanced energy management practices. To address this, this program aims to enhance the understanding of culinary MSME managers in Legok Village about energy efficiency and its practical application by introducing commercially available IoT-based monitoring devices. These devices allow them to track and manage electricity consumption in their culinary businesses effectively. The methods used include theoretical presentations, tool demonstrations, practical exercises, and technology transfer. Evaluation results show that this training is highly effective and increases partner knowledge. Feedback from participants emphasizes the need for improved security, better practicality, and the addition of features such as peak watt monitoring.